Future-oriented emotions: conceptualization and behavioral effects - Baumgartner, Hans; Pieters, Rik; Bagozzi, Richard P. (European journal of social psychology, 2008)
We distinguish between two kinds of future‐oriented emotions (anticipatory and anticipated) and investigate their behavioral effects. Anticipatory emotions are currently experienced due to the prospect of a future event (e.g., hope or fear). Anticipated emotions, on the other hand, are expected to be experienced in the future if certain events do or do not occur (e.g., anticipated joy or regret). We discuss the theoretical differences between the two types of future‐oriented emotions and examine their role in motivating goal‐directed behavior. The results of a longitudinal study (n = 472) and a separate control group analysis (n = 340) provide consistent support for the convergent and discriminant validity of positive/negative anticipatory and anticipated emotions and their independent influence on goal‐directed behavior. Copyright © 2007 John Wiley & Sons, Ltd.